The assembly pathway of complex I in Arabidopsis thaliana. (27th November 2018) - Ligas, Joanna; Pineau, Emmanuelle; Bock, Ralph; Huynen, Martijn A.; Meyer, Etienne H.
Summary: All present‐day mitochondria originate from a single endosymbiotic event that gave rise to the last eukaryotic common ancestor more than a billion years ago. However, to date, many aspects of mitochondrial evolution have remained unresolved. Comparative genomics and proteomics have revealed a complex evolutionary origin for many mitochondrial components. To understand the evolution of the respiratory chain, we have examined both the components and the mechanisms of the assembly pathway of complex I. Complex I represents the first enzyme in the respiratory chain, and complex I deficiencies have dramatic consequences in both animals and plants. The complex is located in the mitochondrial inner membrane and possesses two arms: one embedded in the inner membrane and one protruding in the matrix. Here, we describe the assembly pathway of complex I in the model plant Arabidopsis thaliana . Using a proteomics approach called complexome profiling, we have resolved the different steps in the assembly process in plants. We propose a model for the stepwise assembly of complex I, including every subunit. We then compare this pathway with the corresponding pathway in humans and find that complex I assembly in plants follows a different, and likely ancestral, pathway compared with the one in humans. We show that the main evolutionary changes in complex I structure and assembly in humans occurred at the level of the membrane arm, whereas the matrix arm remained rather conserved. Significance statement: Complex I is the first enzyme in the respiratory chain, and complex I deficiencies have dramatic consequences in humans and plants. Using a combination of proteomics and genetic approaches we determined the assembly pathway of complex I in the model plant Arabidopsis thaliana . We propose a detailed assembly model which can be used to better understand complex I deficiencies.